Analisis Kompetensi Peserta Pelatihan Public Speaking Melalui Kajian Retorika Aristoteles - Mardiningsih, Heni (Balai Diklat Keagamaan Surabaya, 2023)
Public Speaking Technical Training is training that equips trainees with public speaking competence. Lack of knowledge and experience causes participants to have difficulty in mastering speech material, remembering scripts, unable to convey messages with the right intonation or gestures and do not to know how to composing speech texts. This research contributes to explaining how the competence of participants in technical public speaking training needs to be understood and mastered by ASN through a study of Aristotle's rhetorical studies. Aristotle's law of rhetoric consist of inventio, despositio, acutio, memoria and pronuntitio. Based on the results of interviews, observations and documentation, explained that in general, the participants were not familiar and understood the five basic laws of rhetorical studies for public speaking. Even after attending the training, the participants' speaking competence only slightly increased. This shows that the participants' understanding and application of the public speaking training material is still low. While the cognitive abilities of the participants increased after participating in the training, as indicated by the average post-test score of 40 participants of 78, which was higher than the pre-test average value of 52. Hence, it is necessary to have follow-up actions through training and continuous assistance in the practice of public speaking in order to deliver higher quality speaker, writer, moderator or presenter, by applying the five laws of Aristotle's rhetorical studies.